Pengaruh Pemberian Ekstrak Tempe Kedelai Terhadap Kerusakan Sel Ginjal Mencit (Mus musculus) Akibat Pemberian Parasetamol - Ismanaf, Dadang; Widjokongko, S. B.; Sjarifah, Ipop (Nexus Kedokteran Translasional, 2013)
Background:The objectives of this research are to know the influence of soy bean tempeh extract to renal cell damaging of mice (Mus musculus) which is induced by Paracetamol and the increase of soy bean tempeh extract dose can  also increase protection effect  to renal cell damaging of mice (Mus musculus) which is induced by  Paracetamol.   Methods:This was laboratory experimental research with thepost test only controlled group design. Samples were 28 male mice, Swiss webstertype, 2-3 month sold age and ± 20 gr of each weight. Samples were divided into 4 groups of 7 mice each. Sampling technique used in this research was incidental sampling. Mice for control group (K) and the first treatment group (P1) will be given aquadest for 14 days in a row. The second treatment group (P2) and third treatment group (P3) will begiven soy bean tempeh extracts dose for 14 days in a row. Soy bean tempeh extracts dose in each group is 2,2 mg/20 gr weight of mice and 4,4 mg/20 gr weight of mice. Paracetamol  will be given to P1, P2, and P3, with dose 5mg/20 gr weight of mice in 0,1 ml aquadest on the day 12, 13, and 14. On day-15, mice were sacrificed and kidneys were taken to make preparations by paraffin block method and hematoxilin eosin (HE) staining. Kidney histological features were assessed based on quantifying of pyknosis, karyorrhexis, and karyolysis. Data were analyzed using the One-Way ANOVA test (α=0.05) and continued with Post Hoc Multiple Comparisons LSD test (α=0.05). Results:Result of One-Way ANOVA shows that there was a significant of degree between 4 groups with p=0,000 (p<0,05). Result of LSD method there was a significant of degree between K-P1, K-P2, K-P3, P1-P2, P1-P3, and P2-P3 groups with Beach p=0,000 (p<0,05). Conclusions:The feeding of soy bean tempeh extracts was able to decrease the renal cell damaging of mice and the increase of soy bean tempeh extracts dose     followed by the increase of protection effect to the renal cell damaging of mice which is induced by paracetamol. Keywords:soy bean tempeh extracts, paracetamol, renal cell damaging